2010
DOI: 10.1007/s12649-010-9049-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol: An Evaluation of its Scientific and Technological Development and Network of Players During the Period of 1995 to 2009

Abstract: Ethanol is being considered worldwide as a promising fuel and the reasons are twofold: a substantial rise in the price of oil and environmental, social and geographic issues. This study aims to present a scientific and technological evaluation of ethanol development during the period of 1995-2009. The scientific data was collected and processed using statistic tools available at the Web of Science Ò . Research on patents was made on Esp@cenet-the European Patent Office, and the results were processed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…The process starts from the milling generating tons of bagasse which is separated and used for the cogeneration of energy in boilers. When operated at 22 bar and 300 °C to 600 °C, energy selfsufficiency is reached with a tendency for there to be left overs (PERRONE et al, 2010). For the excess of bagasse, an alternative can be developed from the gasification process which is the production of Syngas (CO and H 2 ), widely used in synthesis in chemical industries or for electricity production with the help of turbines (THEVENIN et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The process starts from the milling generating tons of bagasse which is separated and used for the cogeneration of energy in boilers. When operated at 22 bar and 300 °C to 600 °C, energy selfsufficiency is reached with a tendency for there to be left overs (PERRONE et al, 2010). For the excess of bagasse, an alternative can be developed from the gasification process which is the production of Syngas (CO and H 2 ), widely used in synthesis in chemical industries or for electricity production with the help of turbines (THEVENIN et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Brazil's sugarcane industry association (UNICA) reported that the amount of crushed surgarcane in the South-Central region in 2013/14 was 596.936 Mt, about 12% up from the 532.758 Mt produced in 2012/13 [4] that generated approximately 118 Mt of wet bagasse. Even considering its utilization as fuel for energy generation (typically in steam boilers) in the production mills, Perrone et al [5] report that there is still a 12% surplus of biomass that will increase proportionally with the increase of ethanol production, requiring solutions and innovative ideas in order to generate new economic value and opportunities for the sugar and alcohol industry. Elements including N, P, K, S, Ca, Mg, Fe, Zn, B, Cu, Mn, Cl and Si considered as macro-, micro-and functional nutrients are essentials for increasing and sustaining crop yields [6].…”
Section: Introductionmentioning
confidence: 99%
“…3 Estudos indicam que o uso de etanol como substituto da gasolina pode reduzir as emissões de CO 2 cerca de 12 %. 4 Uma alternativa muito interessante seria a utilização do etanol na produção de diversos insumos químicos de maior valor agregado, envolvendo reações de oxidação, desidratação, desidrogenação, dentre outras. Na Figura 1 estão descritos diversos produtos obtidos através de sucessivas reações envolvendo a transformação do etanol.…”
Section: Introductionunclassified
“…11,15 A utilização de zeólitas como suportes ácidos, ao invés de alumina, pode possibilitar a conversão direta de etanol em óxido de etileno, visto que zeólitas possuem diversas características que propiciariam essa catálise, como: grande área superficial, capacidade de adsorção num amplo espectro que vai desde altamente hidrofóbicas a altamente hidrofílicas, estrutura que permite a criação de sítios ativos, tais como sítios ácidos, entre outras. 16 As zeólitas são aluminossilicatos microporosos e cristalinos com estrutura baseada numa extensa rede tridimensional de tetraedros SiO 4 e AlO 4 . 17 A composição química das zeólitas pode ser representada de acordo com a seguinte fórmula geral: x e y = número de átomos de Al e Si por cela unitária, respectivamente; w = número de moléculas Dessa forma, a presença de átomos de alumínio na estrutura da zeólita gera cargas negativas que precisam ser compensadas por cátions.…”
unclassified